1997
DOI: 10.1007/s004140050070
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of remnant-like particles as a risk factor for sudden cardiac death

Abstract: Postmortem plasma lipid and lipoprotein levels were analyzed in two groups of Japanese subjects who died suddenly and unexpectedly due to cardiac (n = 93) or non-cardiac (n = 26) causes. No individuals in either group had a significant medical or cardiac history. In this study, we measured plasma total cholesterol, triglycerides, VLDL-cholesterol, LDL-cholesterol, HDL-cholesterol, and especially triglyceride-rich lipoprotein remnants. Triglyceride and apo E-rich remnant-like particles (RLP) were studied as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…1 RLP-triglyceride is known to be one of the most significant risk factors for sudden cardiac death. 2,3 Kugiyama et al 4 emphasized the importance of remnant lipoprotein level of fasting serum in predicting future coronary events in patients with coronary artery disease independently of other risk factors. Nakajima et al 5 have developed a simple, rapid assay method for determination of RLP-cholesterol (RLP-C), ie, chylomicron and VLDL remnants.…”
mentioning
confidence: 99%
“…1 RLP-triglyceride is known to be one of the most significant risk factors for sudden cardiac death. 2,3 Kugiyama et al 4 emphasized the importance of remnant lipoprotein level of fasting serum in predicting future coronary events in patients with coronary artery disease independently of other risk factors. Nakajima et al 5 have developed a simple, rapid assay method for determination of RLP-cholesterol (RLP-C), ie, chylomicron and VLDL remnants.…”
mentioning
confidence: 99%
“…The prevalence of severe coronary atherosclerosis is known to be strongly associated with age (Table1). We found that plasma lipid (TC, TG) and lipoprotein (LDL-C, RLP-C, and RLP-TG) levels were significantly elevated in these sudden cardiac death cases as compared with those in control death cases when coronary atherosclerosis was pathologically graded above (1+), reflecting the clinical feature of severe coronary atherosclerosis (11)(12)(13). Most of the coronary arteries in PDS cases were pathologically graded as (−) and (±), indicating no coronary atherosclerosis [11].…”
Section: Role Of Plasma Ldl and Remnant Lipoproteins At Coronary Athementioning
confidence: 83%
“…Based on our autopsy studies, more than two thirds of SCD cases were found to be associated with postprandial remnant hyperlipoproteinemia [11][12][13][14][15]. If severe spasm of the coronary artery is to be a crucial event prior to cardiac death in PDS, we may say that the vasospasm is not very likely to occur in coronary arteries with severe coronary artery atherosclerotic lesions due to reduced elasticity and increased stiffness or hardness of the vascular wall.…”
Section: Role Of Plasma Ldl and Remnant Lipoproteins At Coronary Athementioning
confidence: 91%
See 2 more Smart Citations